Pendekatan Student Centered Learning Menggunakan Model Kooperatif Dalam Maharoh Kalam - Maulana, Alfan Habib; Syarifah, Ainun; Farika, Anis (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
he transformation of learning paradigms from teacher-centered to student-centered learning (SCL) positions students as the main actors in constructing knowledge, collaborating, and reflecting on learning outcomes. In the context of Arabic language instruction, particularly maharah kalam (speaking skills), this approach is highly relevant since speaking competence requires continuous interaction and negotiation of meaning. This study aims to improve students’ speaking skills through the integration of SCL with cooperative learning models such as Think-Pair-Share, Jigsaw, Numbered Heads Together, and role-play. The method employed is Classroom Action Research (CAR) conducted over two cycles using both qualitative and quantitative approaches. Qualitative data were collected through observations, interviews, and field notes, while quantitative data were obtained from pre- and post-oral tests in each cycle. The findings indicate that in Cycle I, there was an initial improvement in students’ speaking fluency and confidence, although participation remained uneven and several students struggled with vocabulary. In Cycle II, after the implementation of vocabulary scaffolding, role rotation, performance rubrics, and peer feedback, students demonstrated more significant progress, marked by more stable fluency, more accurate vocabulary use, and more active and collaborative interaction. Challenges such as lack of confidence and unequal participation were minimized through role-based cooperative strategies. These findings affirm that the integration of SCL and cooperative learning models is effective in enhancing maharah kalam and provides practical learning designs that Arabic language teachers can apply in various educational contexts.